Efektivitas terapi seft dan back massage terhadap kelelahan dan spiritualitas pada pasien non-hodgkin’s lymphoma diffuse large b-cell cavum nasi dextra: Studi kasus - Wulandari, Sri; Prasestiyo, Hamudi (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Diffuse Large B-Cell Lymphoma (DLBCL) is the most common and aggressive subtype of Non-Hodgkin's Lymphoma, with nasal cavity involvement being very rare. Non-pharmacological approaches such as Spiritual Emotional Freedom Technique (SEFT) and back massage have been shown to reduce fatigue and improve spiritual well-being, but combination therapy has not been widely studied. Purpose: To determine the effectiveness of the combination of SEFT and back massage on fatigue and spirituality in patients with nasal DLBCL through a case study approach. Method: The research design used a quantitative descriptive pre-post case study. The subject was a 65-year-old male patient diagnosed with right nasal cavity DLBCL. The intervention was administered over three consecutive days, consisting of a combination of SEFT (15–20 minutes) and slow-stroke back massage (20–25 minutes). The instruments used were the Fatigue Assessment Scale (FAS) and the Spiritual Well-Being Scale (SWBS). Results: There was a decrease in the FAS score from 40 to 32 and an increase in the SWBS score from 69 to 98. Although both interventions were still in the severe and moderate categories, the decrease and increase in post-test scores showed a positive trend after three intervention sessions. Conclusion: The combination of SEFT and back massage effectively reduced fatigue and increased spirituality in patients with nasal cavity DLBCL. This intervention is safe, applicable, and supports a holistic nursing approach. Keywords: Back Massage; DLBCL; Fatigue; SEFT; Spirituality. Pendahuluan: Diffuse Large B-Cell Lymphoma (DLBCL) merupakan subtipe paling umum dan agresif dari Limfoma Non-Hodgkin, dengan keterlibatan kavum nasi yang sangat jarang. Pendekatan non farmakologis seperti Spiritual Emotional Freedom Technique (SEFT) dan back massage telah terbukti dapat menurunkan kelelahan dan meningkatkan kesejahteraan spiritual, tetapi belum banyak diteliti dalam pemberian kombinasi. Tujuan: Mengetahui efektivitas kombinasi SEFT dan back massage terhadap kelelahan dan spiritualitas pada pasien DLBCL cavum nasi melalui pendekatan studi kasus. Metode: Desain penelitian studi kasus pre–post deskriptif kuantitatif. Subjek adalah pasien laki-laki, 65 tahun, dengan diagnosa DLBCL cavum nasi dextra. Intervensi diberikan selama tiga hari berturut-turut berupa kombinasi SEFT (15–20 menit) dan back massage slow-stroke (20–25 menit). Instrumen yang digunakan yaitu Fatigue Assessment Scale (FAS) dan Spiritual Well-Being Scale (SWBS). Hasil: Terjadi penurunan skor FAS dari 40 menjadi 32 dan peningkatan skor SWBS dari 69 menjadi 98. Meskipun kedua intervensi ini masih dalam kategori berat dan sedang tetapi penurunan dan peningkatan dalam skor post-test menunjukan arah yang positif setelah tiga sesi intervensi. Simpulan: Kombinasi SEFT dan back massage efektif dapat menurunkan kelelahan dan meningkatkan spiritualitas pada pasien DLBCL kavum nasi. Intervensi ini aman, aplikatif, dan mendukung pendekatan keperawatan yang holistik. Kata Kunci: Back Massage; DLBCL; Fatigue; SEFT; Spiritualitas.